Socio-economic Status Scales in India & Globally: A Review - Rachita Lakhumna; Prasad D. Pore; Saurabh K. Wadhwa (Preventive Medicine: Research & Reviews)
Socio Economic Status (SES) Scales as used for investigating social status and related health conditions are comprehensively reviewed for their background, development, strengths, weaknesses and popularity. They measure components such as education, occupation, income and possessions either individually or in combination for urban/rural population. Level of socio-economic status is in turn related to health status. Although carrying limitations, yet Kuppuswamy, BG Prasad and Udai Pareek remain the most accepted, updated and longstanding Indian scales. Others scales such as Tiwari and Kumar, Gaur and Agarwal can also be harnessed. Below Poverty Line (BPL) scale and multidimensional poverty index, Hashim and identical scales should also be applied to identify BPL families for delivering medical benefits through a government initiative such as- Ayushman Bharat Pradhan Mantri Jan Arogya Yojana. Few international scales are also discussed. Nevertheless, a combination of scales or an all-encompassing scale with the most relevant classification of the Indian society and identification of the poor is always desired by researchers and policy makers for a reasonable outcome.